2019
DOI: 10.1038/s41598-018-36709-1
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital schistosomiasis is associated with signatures of microbiome dysbiosis in Nigerian adolescents

Abstract: Urogenital schistosomiasis is a neglected tropical disease caused by the parasite Schistosoma haematobium, which resides in the vasculature surrounding the urogenital system. Previous work has suggested that helminthic infections can affect the intestinal microbiome, and we hypothesized that S. haematobium infection could result in an alteration of immune system-microbiota homeostasis and impact the composition of the gut microbiota. To address this question, we compared the fecal microbiomes of infected and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 136 publications
(95 reference statements)
2
51
2
1
Order By: Relevance
“…Additionally, even at the genus level, no major changes were detected, indicating that in our context, there is no gut dysbiosis in S. japonicum infection-induced liver cirrhosis patients. This result is somehow unexpected and different from other studies that have reported gut dysbiosis in the context of human schistosomiasis (e.g., those caused by S. mansoni and S. haematobium) [20,21,22,23,24]. Additionally, in vivo studies have reported Schistosoma infection-related alterations in gut microbial composition.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…Additionally, even at the genus level, no major changes were detected, indicating that in our context, there is no gut dysbiosis in S. japonicum infection-induced liver cirrhosis patients. This result is somehow unexpected and different from other studies that have reported gut dysbiosis in the context of human schistosomiasis (e.g., those caused by S. mansoni and S. haematobium) [20,21,22,23,24]. Additionally, in vivo studies have reported Schistosoma infection-related alterations in gut microbial composition.…”
Section: Discussioncontrasting
confidence: 90%
“…Different studies focused on different Schistosoma spp. that have different organ tropisms: e.g., S. mansoni and S. japonicum target the gut and liver, while S. haematobium targets the bladder and the urogenital system [20,21,22,24]. Importantly, the notion that S. haematobium infection was equally associated with human gut dysbiosis suggests that potential alterations of intestinal microbial communities in the context of schistosomiasis are probably a consequence of infection-induced systemic immune responses (and not of local events).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations